Viruses and Their Interactions With Bacteria and Archaea of Hypersaline Great Salt Lake - Bhattarai, Bishav; Bhattacharjee, Ananda S.; Coutinho, Felipe H.; Goel, Ramesh K. (Frontiers in Microbiology, 2021)
Viruses, as obligate parasites, play a vital role in the biogeochemical cycle by expressing auxiliary metabolic genes during infection, enhancing the lateral transfer of genes to the host, and inducing host mortality. Although advancements have been made in delineating bacteria and archaea's role in the global biogeochemical cycle, the study on viruses' role is still in the fledgling stage, especially for the hypersaline systems of the Great Salt Lake (GSL) ecosystem in Utah, USA, a model hypersaline lake. In this study, we elucidate the diversity of viruses and describe virus-host interaction in the GSL sediments along a salinity gradient. The GSL sediment virosphere consisted of Haloviruses (32.07 ± 19.33 %), Siphoviridae (39.12 ± 19.8 %), Myoviridae (13.7 ± 6.6 %), and Podoviridae (5.43 ± 0.64 %). Our study shows, the concentration of organic carbon and inorganic nutrients (nitrogen and phosphorus) governs the viral, bacteria, and archaeal diversity along with salinity. Microbial host predictions for the GSL viruses expand our current host range knowledge. Although the abundance of lysogens in the GSL sediment virosphere was low (17.52 ± 3.75 %), identification of auxiliary metabolic genes for photosynthesis (psbA), carbon fixation (rbcL, cbbL), formaldehyde assimilation (SHMT), and nitric oxide reduction (NorQ) signifies the role of GSL viruses in the biogeochemical cycle. The study delineates viruses, bacterial, and archaeal diversity of hypersaline sediments of the GSL, Utah, USA. Nutrients (N, P) and available organic carbon contribute to shaping the viral, bacterial, and archaeal diversity along the salinity gradient of the GSL. The hypersaline GSL virosphere expands our current knowledge regarding a) the host range and b) auxiliary metabolic genes. This study provides a foundation for the detailed culture-based physiological study of viruses, bacteria, and archaea from the GSL with information on their growth conditions and nutritional requirements.